Sosialisasi Wakaf Tunai Pada Majelis Taklim Istiqomah Kelurahan Tanjung Sari, Medan - Heriyati Chrisna; Hernawaty Hernawaty; Noviani Noviani (Pelita Masyarakat, 2021)
This community service was carried out in the Majelis  Taklim  Istiqomah which is a maternal recitation group in Tanjung Sari Medan Village. This pemeral in the Majelis  Taklim  Istiqomah departed from the results of the research that had been carried out. The results of the study proved that the factors that included revenue, religiusity and knowledge had a positive and significant effect on the interest in cash in the congregation of the Majelis  Taklim  Istiqomah while the subjective norm factor had a negative and insignificant effect on the interest in cash in the congregation of the Majelis  Taklim  Istiqomah. Simultaneously, income factors, subjective norms, religiosity and knowledge influence the interest in working in cash in the jamaah Majelis  Taklim  Istiqomah. Revenue factors, subjective norms, religiusity and knowledge are able to explain the interest in cash in the pilgrims of the Majelis  Taklim  Istiqomah amounted to 65.6% while the remaining 34.4% is explained by other factors or variables which are not included in this study. From the initial observation and interview results with some members of the recitation and reinforced with the results of the research can be taken by a conclusion that the knowledge of the mothers of taklim assemblies about cash waqf still very low, can even be said to be very low, because they still argue that waqf only in the form of mosques, graves or schools. From these problems, the service team has socialized the cash waqf in the mothers of Majelis  Taklim  Istiqomah, and the socialization went smoothly and followed by being very enthusiastic about the the mothers of Majelis  Taklim  Istiqomah.